Heat transfer experiment with the prototypical Ra number of heavy metallic layer in IVR strategy. (April 2022) - Li, Zongyang; Chang, Huajian; Chen, Lian; Han, Kun; Fang, Fangfang
Abstract: In-Vessel Retention (IVR) strategy is significant to limit molten corium in the Reactor Pressure Vessel (RPV) during severe accident scenarios. A heat transfer experiment has been established to study the thermal load on the cooled wall adjacent heavy metallic layer. The test section of the heavy metallic layer experiment is a hemisphere, and its diameter is 2.4 m; the height of simulant is set to 0.3 m. Heavy metallic layer experiment uses water as the simulant, and it uses the internal heating coils to represent the decay heat. Three independent sidewall coolant channels are used to cool the whole test section. The top boundary condition of the test section could be a cooling or insulated condition. The experimental results illustrate that the Mayinger heat transfer correlation could predict the heavy metallic layer experiment results, and it is recommended to predict the sideward heat flux. Applicating the heat transfer correlation and experimental q local / q mean distribution to the heavy metallic layer in core degradation situation, the heat transfer correlation calculated results demonstrate that it is unlikely for the local sideward heat flux to exceed the Critical Heat Flux (CHF). The possible top cooling boundary for the heavy metallic layer contributes to alleviating wall melting. Generally, it is unlikely that the vessel failure occurs at the cooled wall adjacent the heavy metallic layer.